Chúc bạn học tốt!
$\dfrac{3x - 2y}{4} = \dfrac{4x - 5y}{3} = \dfrac{3z + 1}{2}$ (1)
$\rightarrow 3(3x - 2y) = 4(4x - 5y) \rightarrow 9x - 6y - 16x + 20y = 0 \rightarrow - 7(x - 2y) = 0 \rightarrow x = 2y$
4x + 7y = -3
$\rightarrow 15y = -3 \rightarrow y = \dfrac{-3}{15} = - 0,2$
Thế x = 2y vào phân thức đầu tiên của dãy tỉ số (1) ta dc :
$\dfrac{3.2y - 2y}{4} = y = \dfrac{4x - 5y}{3} = \dfrac{3z + 1}{2} = - 0,2$
$\rightarrow 4x - 5y = - 0,6 \leftrightarrow 3y = -0,6 \leftrightarrow y = -0,2$
$3z + 1 = - 0,4 \leftrightarrow z = \dfrac{-7}{15}$